WATU GOYANG: WISATA NEGERI KHAYANGAN (PENGEMBANGAN DESA WISATA TAPAK TILAS SULTAN AGUNG, MANGUNAN) - Lailam, Tanto; Darumurti, Awang; Yunita, Ani (Universitas Muhammadiyah Tapanuli Selatan, 2020)
Community service program focused on developing competitive and cultured leading of tourism village. The partner of this service is